(untitled) (ModaPalavra e-periódico, 2017)
This is an interview with Prof. Dr. Nelson Pinheiro Gomes, from the University of Lisbon. The approach is on Trends Studies as an academic area, which is a new discipline, in process of sedimentation. The professor discusses his academic path, going from fashion to the study of sociocultural trends, as well as what he seeks in this discipline in terms of international practices and consolidation of the area. The interviewee gives his opinion about the birth of trends, the importance of the analysis of the Cultural DNA of a society and the practical application of this area of studies. Finally, he gives his opinion about the moment Lisbon goes through and the context of Trend Studies.